United States and the military and security assistance to Latin America and the Caribbean: critical approach, 2010-2022 - Lajtman, Tamara (2024)
Counter-narcotics plans, the redefinition of threats to the U.S., and Chinese and Russian presence in Latin America and the Caribbean have reignited the debate on security assistance, which involves economic and military components. Several actors and the U.S. government allege ‘failed’ results regarding the drug war, and they recommend increasing the amount of such assistance. This article reviews the definition and how government, academia, and think tanks distinguish military from economic support. Official data from 2010-2022 show that 90% of foreign assistance correspond to economic assistance and 10 per cent to military assistance. To contrast this information, we propose the reclassification of the assistance items, through a critical analysis that yields different results where in the same period security assistance amounts to 35% of the total. This is an index of the systematic way, throughout different U.S. administrations, in which security goods and services tend to be placed in non-military security programs, as part of economic assistance, when by origin and objectives, they correspond with the military sphere.